Investigation on the Use of Graphene Oxide as Novel Surfactant for Stabilizing Carbon Based Materials. Issue 10 (2nd October 2016) - Mohd Zubir, Mohd Nashrul; Badarudin, A.; Kazi, S. N.; Nay Ming, Huang; Sadri, Rad; Amiri, Ahmad
Abstract : The present work reported on the use of graphene oxide (GO) as effective dispersant to isolate different carbon allotropes. The nature of its chemical structure which consists of hydrophobic and hydrophilic components enables GO to behave as surfactant, paving routes for dissolution of graphitic materials and achieving surfactant free all-carbon solutions. Two additional carboneous materials under the family of fullerene (carbon nanofiber—CNF) and graphite (graphene nanoplatelets—GnP) were introduced within the present study to form a new GO based hybrid complexes on top of the commonly investigated carbon nanotube (CNT) based GO hybrid. Investigation on GO stability with respect to particle size and zeta potential measurements showed that the strength of its dispersibility was highly dependent on its morphological size and less affected by the pH. Rheological study revealed that GO shear–strain relationship is highly sensitive to the particle size. The GO viscosity experienced dramatic changes from Newtonian toward shear thinning behaviors as the particle size increases. Thermal conductivity measurement highlighted as high as 8% increase in magnitude with the addition of CNT, CNF, and GnP carbon constituents, indicating that the enhancement may be attributed to the much efficient thermal transport along the conducting path of pristine carbon allotropes. GRAPHICAL ABSTRACT: